2008
DOI: 10.1590/s0102-311x2008001600002
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis and neonatal screening

Abstract: The clinical and diagnostic aspects of cystic fibrosis have been extensively reviewed, with an emphasis on neonatal screening. This systematic literature review involved a search for relevant contributions in the PubMed and SciELO databases. The first references to cystic fibrosis date to the Middle Ages. Cystic fibrosis is the most frequent autosomal recessive hereditary disease among Caucasians (1:2,000 to 3,500). More than 1,000 mutations lead to the disease, the most common being "F508, with 70% prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
(79 reference statements)
0
7
0
2
Order By: Relevance
“…56 MG and SC are additional states that offer neonatal screening for CF (Phase III of NCFSP); the mean age at diagnosis was 51.4 days and 64 days, respectively, using the IRT/IRT protocol; 57,58 in SP, in a pilot study for implementation of CF screening, the mean age at diagnosis was 69 days. 59 These are states that have a population coverage higher than 80% and have diagnosed the cases expected in the region, according to the expected frequency of CF in that State (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…56 MG and SC are additional states that offer neonatal screening for CF (Phase III of NCFSP); the mean age at diagnosis was 51.4 days and 64 days, respectively, using the IRT/IRT protocol; 57,58 in SP, in a pilot study for implementation of CF screening, the mean age at diagnosis was 69 days. 59 These are states that have a population coverage higher than 80% and have diagnosed the cases expected in the region, according to the expected frequency of CF in that State (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…5 The diagnosis may be made in association with the clinical picture and the evaluation of the concentration of chloride in the sweat 6 or through Neonatal Screening using the immuno-reactive trypsinogen test. 7 The diagnosis of cystic fibrosis significantly affects the routine of the entire family, principally that of the mother-child binomial, as the ill person is usually obliged to live in a routine of hospitalization, painful treatment, and sequelae which impose limitations and require long periods of supervision and care, 8 interruption of routine activities, financial hardship, pain and living with the real possibility of death. 9 Various studies have been undertaken in Paraná addressing cystic fibrosis, either in isolation or in the context of Neonatal Screening.…”
Section: Introductionmentioning
confidence: 99%
“…It is a result of mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene located on chromosome 7 (2-4). More than 1000 mutations have been described (5), the most common being F508del, which shows a prevalence of 70% among Caucasians (6) and of approximately 23-55% among Brazilians (7). A recent study using a two-tier survey design in five Brazilians States (Minas Gerais, São Paulo, Paraná, Santa Catarina, and Rio Grande do Sul) suggested that nearly 48% of the CF alleles carry the F508del mutation and estimated that the disease incidence for Brazilians of European descent is 1 in 7576 live births.…”
mentioning
confidence: 99%